CABBAGE GROWTH and PRODUCTION IN RELATION TO PLANT DENSITY and NITROGEN - Cecilio-Filho, Arthur B. [UNESP]; Luiz-Cavarianni, Rodrigo [UNESP]; Gaetano de-Castro, Julio C. [UNESP]; Mendoza-Cortez, Juan W. [UNESP] (Colegio de Postgraduados, 2011)
At present, the Brazilian market prefers cabbage (Brassica oleracea var. capitata) of smaller size, which can be achieved by increasing population density; yet this management can alter the optimum rate of nitrogen (N), its second most required nutrient. This study was conducted in the Universidade Estadual Paulista, Jaboticabal, São Paulo, Brazil, from February to June 2004. The objective was to evaluate the effect of population density: 31 250 (DI) and 46 875 plants ha(-1) (D2) with 0, 100, 200 and 300 kg N ha-1 on the growth and production of cabbage Astrus. The experimental design consisted of randomized blocks with a 2 x 4 factorial arrangement and three replicates. Statistical analysis were a variance analysis (F test), the Tukey test for population density averages and polynomial regression for the N rates. In D1, an increase was recorded in the number of inner and outer leaves, dry matter of inner and outer leaves, the stem diameter at the insertion of the head, and the stem dry and fresh matter. The maximum size of the plant in D2 was 1.57 kg and was obtained with 300 kg N ha(-1), while in D1 it was 2.1 kg and was obtained with 244 kg N ha(-1). The optimal economic rate in 131 was 227.1 kg N ha(-1). The highest yield (72.7 t ha(-1)) was obtained with the highest N rate in D2. Smaller cabbage heads, commercially preferred, were obtained without the application of N, regardless of plant population.
Keywords: Brassica oleracea var. capitata; distance between plants; Nitrogen fertilization